2010
DOI: 10.1016/j.avb.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression in home visitation: A systematic review

Abstract: Depression is prevalent in new mothers and has been shown to have profound negative impacts on parenting, maternal life course, and child development. High rates of maternal depression have been found in home visitation, a widely disseminated prevention approach for high risk mothers and their children. This paper reviews the emerging literature on the prevalence, impact, and treatment of depression in the context of home visitation. Findings are synthesized and methodological and design limitations are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
124
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 73 publications
7
124
1
Order By: Relevance
“…22,39 Although some studies suggest that HV can reduce maternal depression, 57 and that it is a promising intervention for reaching depressed parents who might not otherwise gain access to the help they need, 44 the results of large-scale evaluations generally indicate that parental depression is a serious impediment to HV program effectiveness. 21 Our study findings also revealed an association between maternal depression and child maltreatment, though the relation differed for mothers who received HV comparedwith mothersinthe control group. Among nondepressed mothers, when controlling for maternal race and age at first birth, those in the HV program were less likely than those in the control group to have a child with a CPS report.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…22,39 Although some studies suggest that HV can reduce maternal depression, 57 and that it is a promising intervention for reaching depressed parents who might not otherwise gain access to the help they need, 44 the results of large-scale evaluations generally indicate that parental depression is a serious impediment to HV program effectiveness. 21 Our study findings also revealed an association between maternal depression and child maltreatment, though the relation differed for mothers who received HV comparedwith mothersinthe control group. Among nondepressed mothers, when controlling for maternal race and age at first birth, those in the HV program were less likely than those in the control group to have a child with a CPS report.…”
Section: Discussionsupporting
confidence: 56%
“…39,42 On the other hand, maternal depression, common among young mothers and a risk factor for maltreatment, may impede the ability of programs to reduce child abuse and neglect. 21,22,36,[43][44][45] Maternal depression increases the risk for parenting difficulties and is strongly associatedwithchildmaltreatment. 15,[46][47][48][49][50] Of parents investigated by CPS whose children remain in their custody, an estimated 25% report having experienced major depression within the past year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average high treatment participant began engaging with the program half way into her pregnancy and had received, on average, 27 home visits between program entry and 18 months. It is possible that this small window of intervention did not allow enough time for the participants to adopt the strategies advised by their mentors as the bond between mentor and participant was still forming (Ammerman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…3 These child risk factors may arise from dynamics in their own families, including maternal depression and clinical and social correlates of this depression: trauma and intimate partner violence, poor birth outcomes, and infant mortality. 4 Maternal depression, often underdiagnosed and untreated in the first several years of life, is a particularly prevalent concern, with estimates ranging from 15% in the general population to double that in low-income mothers. 5 As pediatric providers begin to incorporate the latest findings from neuroscience into their efforts to establish high-quality medical homes for their patients, they find themselves serving many families who may be at risk for toxic stress and who are experiencing psychosocial challenges.…”
mentioning
confidence: 99%